Influence of INM on sugarcane productivity and soil fertility under Indo-Gangetic plain - PAL, RAJINDER; SINGH, ONKAR; SANGHERA, GULZAR S; GUPTA, R K (The Indian Journal of Agricultural Sciences, 2021)
A field experiment was conducted during 2016-17 at Punjab Agricultural University, Regional Research Station, Kapurthala, Punjab, India with nine treatments comprising various combinations of farmyard manure (FYM), biofertilizers and different levels of chemical fertilizers in a randomized block design (RBD). Our results demonstrated that application of FYM @ 20 t/ha with soil test based application of nutrients recorded significantly highest number of millable canes of 134.3 thousand/ha and number of shoots (142.2 thousand/ha) at 150 DAS. However, cane length, cane diameter, single cane weight, cane yield and sugar yield were statistically at par with either application of 100% RDF plus FYM @ 20 t/ha or with the soil test based application of nutrients along with biofertilizers and 10 t/ha of FYM. With 20 t/ha of FYM and chemical fertilizer, the build-up of organic carbon content, N, P, K, Zn, Fe, Cu and Mn were significantly higher than the treatments containing either 10 t of FYM/ha or no manure. Application of FYM or biofertilizers or both along with RDF or STB nutrient application resulted in 12.8 to 17.9% higher cane yield, resulting in additional net returns of ₹ 20592 to 45230/ha as compared to recommended dose of inorganic fertilizers alone. Our study showed that higher cane and sugar productivity and economic returns can be achieved by applying either 20 t of FYM or 10 t of FYM along with bio-fertilizers.